Minimally Invasive Mitral Valve Surgery in Truly High-Risk Patients: Are We Pushing the Boundaries? An Observational Study. Issue 5 (September 2015) - Moscarelli, Marco; Margaryan, Rafik; Cerillo, Alfredo; Kallushi, Enkel; Farneti, Pierandrea; Solinas, Marco
Objective: This study aimed to assess in a retrospective series of truly high-risk patients who underwent minimally invasive mitral valve surgery: (1) postoperative and long-term results and (2) logistic EuroSCORE and EuroSCORE II discrimination power. Methods: Between 2003 and 2013, we reviewed in our institution patients who underwent minimally invasive mitral valve surgery with or without tricuspid valve repair via right minithoracotomy with logistic EuroSCORE of 20 or higher. Results: Among a total number of 1604, 88 patients were identified. Median logistic and EuroSCORE II was 27.29 (interquartile range, 15.3) and 12.7% (11.3%), respectively. Mean (SD) age was 71.9 (8.4) years; 42 were female (47.7%); 60 patients (68.1%) underwent previous sternotomy. Mitral valve was replaced in 59 (67%) and repaired in 29 (32.9%) patients; tricuspid valve repair was performed in 23 patients (26.1%). Median cardiopulmonary bypass and cross-clamp times were 157 minutes (interquartile range, 131–187 minutes) and 83 minutes (81–116 minutes), respectively; conversion to sternotomy and reopening for bleeding was necessary in 4 (4.5%) and 3 (3.4%) patients; permanent and transient neurological injuries were reported in 6 (6.8%) and 3 (3.4%) patients; acute kidney injury was reported in 13 patients (14.7%); 15 patients (17%) had pulmonary complications. Ten patients died while in the hospital (11.2%). Survival at 6 years was 78% (95% confidence interval, 69–88). Conclusions: In this series of truly high-risk patients, minimally invasive mitral surgery was associated with acceptable early mortality and morbidity as well as long-term outcomes; both logistic and EuroSCORE II showed suboptimal discrimination power.